A Graphical Method of Stem Analysis - Mathauda, G. S. (Indian Forester, 1950)
A graphical method of stem analysis described. As compared with the orthodox methods, the fieldwork involved in this method is easier and it yields much more comprehensive information about diameter, height and volume increments.